Seeing through the network: Competitive advantage in the digital economy - Thorsten Koch; Josef Windsperger (Journal of Organization Design, 2017)
Firms operate in an environment that is increasingly permeated with digital technology. The incorporation of digital technology into products, services, and operations has significant implications on how firms can attain and sustain competitive advantage. Traditional strategic models of competitive advantage - such as the industry structure view, the resource-based view or the dynamic capabilities approach - are built on assumptions which lack validity in today's digital environments. Digitization radically changes the very nature of products, the process of value creation and, above all, firms' competitive environment. This study contributes to a better understanding of how firms may achieve sustained competitive advantage in this digital economy: It outlines a network-centric view which explains the competitive environment of firms being confronted with digital technology and its affordances. Based on the network-centric view, the firms may achieve competitive advantage by actively shaping the digital environment (i.e. applying a logic of effectuation) and by value co-creating of the interconnected firms in the digital environment. The framework may help firms to design and create strategies in order to attain and sustain competitive advantage in a digital economy.
Keywords: 650; Digitization; Competitive advantage; Interorganizational networks; Service logic; Digital ecosystems; Effectuation; Network theory